2010
DOI: 10.5137/1019-5149.jtn.3429-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intratechal baclofen (itb) therapy in spacticity

Abstract: AIm: Spasticity is associated with various neurological conditions. Intrathecal baclofen (ITB) is one of the popular treatments for severe spasticity. In this paper we present our experience in treating 30 patients with both spinal and supraspinal spasticity with chronic infusion of Baclofen to evaluate the long term efficacy of this treatment on spasticity, disability and pain, and to evaluate the side effects of intrathecal Baclofen. mAterIAl and methOds: The medical records of 30 patients who underwent bacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
7
0
2
Order By: Relevance
“…Studies of children with neurological conditions other than CP reported that outcome measures of spasticity and dystonia were all level IV to V, with small sample sizes (varying from 1–16 patients). Improvement of spasticity (measured with MAS and Ashworth score) was observed in several stable neurological disorders: anoxic brain damage, traumatic brain injury, and near‐drowning, showing moderate‐to‐large effect sizes (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of children with neurological conditions other than CP reported that outcome measures of spasticity and dystonia were all level IV to V, with small sample sizes (varying from 1–16 patients). Improvement of spasticity (measured with MAS and Ashworth score) was observed in several stable neurological disorders: anoxic brain damage, traumatic brain injury, and near‐drowning, showing moderate‐to‐large effect sizes (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…For the studies for which we were able to compute effect sizes, small‐to‐very‐large effect sizes were found for reduction of spasticity, measured with the Ashworth or Modified Ashworth Scale (MAS) in children with CP (Fig. ) . Broad confidence intervals (CIs) were found for most outcomes, owing to small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, baclofen doses were much higher in patients with cerebral spasticity than in those with spinal spasticity. In another retrospective study, review of medical records from 30 patients with supraspinal or spinal cord injury‐related spasticity who began IT baclofen therapy after inadequate response to oral antispasticity agents revealed that significant improvements from baseline to one year were noted in spasticity scores, spasm frequency, motor function, and pain (201). IT baclofen appeared to be effective in treating both cerebral‐ and spinal‐associated spasticity.…”
mentioning
confidence: 99%
“…Hastanın pozisyonlanmasını, oturmasını, hemşirelik bakımını, hijyen faaliyetlerini, kontinansı ve günlük yaşam aktivitelerini bozabilir, kontraktür ve skolyoz gelişimine sebep olabilir, bası yarası oluşumuna zemin hazırlayabilir ve inkomplet hastalarda ambulasyonu olumsuz etkileyebilir. Aynı zamanda ani ve durdurulamayan spazmlar, ağrıya ve uyku düzeninin bozulmasına sebep olabilir (1)(2)(3)(4)(5).…”
Section: Introductionunclassified
“…Bu yöntemle kan-beyin bariyeri engeli aşılmış ve çok düşük baklofen dozları ile çok daha yüksek serebrospinal sıvı konsantrasyonu elde etme olanağı sağlanmıştır. Yapılan çalışmalarda şiddetli spastisitede intratekal baklofen (İTB) tedavisi güvenilir ve etkili bulunmuştur (2,5,(11)(12)(13).…”
Section: Introductionunclassified